Dry molten globule-like intermediates in protein folding, function, and disease - Acharya, Nirbhik; Jha, Santosh Kumar (Journal of Physical Chemistry B, 2022)
The performance of a protein depends on its correct folding to the final functional native form. Hence, understanding the process of protein folding has remained an important field of research for the scientific community for the past five decades. Two important intermediate states, namely, wet molten globule (WMG) and dry molten globule (DMG), have emerged as critical milestones during protein folding-unfolding reactions. While much has been discussed about WMGs as a common unfolding intermediate, the evidence for DMGs has remained elusive owing to their near-native features, which makes them difficult to probe using global structural probes. This Review puts together the available literature and new evidence on DMGs to give a broader perspective on the universality of DMGs and discuss their significance in protein folding, function, and disease.